Substrate but not seed size affects seed germination of Dypsis onilahensis (Jum. & H. Perrier) Beentje & J. Dransf - Petterson Baptista da Luz; Thalita Neves Marostega; Bruno Nicchio; Leonarda Grillo Neves (Semina: Ciências Agrárias, 2015)
Dypsis onilahensis, commonly known as sibara palm, is a palm tree with enormous ornamental potential. Commercial propagation occurs through seeds, but few studies have evaluated the factors that affect the germination process of this species. Thus, we aimed at evaluating the effects of seed size and substrate on D. onilahensis germination. We used a completely randomized experimental design and a 2 x 3 factorial scheme with two seed sizes (> 15 mm and < 15 mm in diameter) and three substrate types (sand, Plantmax®, and vermiculite), with four replications of 15 seeds. We analyzed germination percentage (G%), number of germinated seeds (NGS), and germination speed index (GSI). Data underwent variance analysis, and means were compared by the Tukey test at 5% probability. Germination began 73 days after sowing. Seed size had no effect on germination. Among substrates, vermiculite showed the best results for GSI, NGS, and G%, followed by sand and then by Plantmax®. Our study provides the first data on factors that affect the germination of this palm tree species.